2019
DOI: 10.1101/523464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disharmony of the world’s island floras

Abstract: Aim: Disharmony is a key concept in island biology that describes the imbalance in the representation of higher taxa on islands compared to their mainland source regions. Although there are strong theoretical arguments for the differential colonization success of different taxa on islands, the empirical evidence for disharmony remains largely anecdotal. Here, we develop a novel method for delineating island source regions and present the first global quantitative assessment of island disharmony.Location: Globa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Most respondents agree that effects of increases in alien species richness will occur mainly on oceanic islands, followed by atolls and continental islands. Oceanic islands show a higher degree of endemism and more disharmonic floras and faunas than the other island types (König et al, 2019;Taylor et al, 2019). This disharmony and proportion of endemism increases with island isolation (Kier et al, 2009;König et al, 2017) and at the same time isolation has been shown to increase island invasibility (Moser et al, 2018).…”
Section: Effects Of Increases In Alien Species Richnessmentioning
confidence: 99%
“…Most respondents agree that effects of increases in alien species richness will occur mainly on oceanic islands, followed by atolls and continental islands. Oceanic islands show a higher degree of endemism and more disharmonic floras and faunas than the other island types (König et al, 2019;Taylor et al, 2019). This disharmony and proportion of endemism increases with island isolation (Kier et al, 2009;König et al, 2017) and at the same time isolation has been shown to increase island invasibility (Moser et al, 2018).…”
Section: Effects Of Increases In Alien Species Richnessmentioning
confidence: 99%
“…The latter may be particularly useful for species distribution modelling where random pseudo-absences are commonly used when true absences are not known (Lobo et al, 2010;Barbet-Massin et al, 2012). Furthermore, GIFT can be used to define regional species pools of local plant communities (Karger et al, 2016), for example, for identifying likely source regions of species that colonize oceanic islands (König et al, 2019). Defining the regional species pool or inferring the floristic status may not only be important for macroecological studies but also for field projects at the local to regional scale.…”
Section: Applications and Outlookmentioning
confidence: 99%
“…Processes such as rare dispersal events, environmental filtering, and in-situ speciation have generated unique, highly endemic plant assemblages on islands worldwide (Weigelt et al, 2015). The biased representation of higher taxa compared to the source pool on islands due to dispersal, environmental, and biotic filters, i.e., disharmony, (Carlquist, 1974;König et al, 2021;Kraft et al, 2015) may result in closely-related species occupying different ecological niches, potentially increasing ecosystem functioning. Yet, unfilled niche space may persist on oceanic islands due to limited colonization and low species diversity.…”
Section: Introductionmentioning
confidence: 99%